Characterization of cardoon accessions as feedstock for biodiesel production - Mancini, Micaela; Lanza Volpe, Melisa; Gatti, Bernardita; Malik, Yair; Moreno, Ana Carina; Leskovar, Daniel; Cravero, Vanina Pamela (Elsevier, 2018)
Diesel fuels have an essential function in industrial economies. In the last decade, several studies were conducted in order to find alternative sources of vegetables oils suitable to biodiesel conversion. The present work aimed to characterize the oil chemical composition in eleven different accessions of domestic and wild cardoon (Cynara cardunculus L. var. altilis and var. sylvestris, respectively) in order to evaluate its putative use as an alternative energy crop, with main focus in biodiesel production. No significant differences were measured between both botanical varieties for oil content; values of 20.80 ± 6.65% were found. The highest values were observed for the wild cardoon accessions “Uruguay Centro” (35.95%) and “Pergamino” (27.78%). The fatty acid composition was similar for both botanical varieties: palmitic (10.9%), stearic (3.0%), oleic (23.5%) and linoleic (61.3%). Comparing with traditional energy crops (soybean, sunflower and rapeseed) the cardoon fatty acid profile is similar to those obtained for soybean. Several biodiesel quality parameters were calculated or estimated over different oil samples. In this way, the acidity ranged from 0.1 to 0.7 mg OH/goil, showing differences among accessions but not between botanical varieties. “Cardo Blanco Peralta” and A-41 (cultivated cardoon) presented the lowest unsaturated degree, iodine values and oleic/linoleic acid relation in their oil; consequently, they showed the most suitable values for the biodiesel quality parameters (cetane number and kinetic viscosity). Based on seed oil composition, this characterization, allowed demonstrating that cardoon oil has appropriate characteristics to be used as feedstock for the production of biodiesel, as well as, to detect accessions with superior quality properties.